Active Training and Forensic Medicine at the Dokuz Eylul University Faculty of Medicine - Yemişçigil, Ali (The Bulletin of Legal Medicine, 1997)
During the last decades it was realised that specialty- and discipline-dominated education was inadequate for training the future doctors, so that new education models were improved. One of these is active training. After a serious period of preparation Dokuz Eylül University Faculty of Medicine started “Active Training” method, emerging around problem-based sessions. It is hard to mention an ideal education program for the medical education. However, a suitable program for problem-based learning is an important step for this purpose. Problem-based learning gives the students an opportunity to get the multidisciplinary knowledge while trying to understand the problems of the case that may be encountered in real life and’ to solve them. The forensic medicine education integrated to the curriculum, will be a part of the whole education lasting for 6 years. Because of this change, revision of the forensic medicine education programme and identification of the knowledge and skills that the practitioners should get are necessary. This change process will affect all of the faculties, and as a result , it will help the solution of standardization problem in education and graduation of qualified doctors. Scientific thinking skills and curiosity of the doctors will influence future development in health sciences. Key words: Medical education, forensic medicine, problem-based learning.